2015
DOI: 10.1111/myc.12339
|View full text |Cite
|
Sign up to set email alerts
|

Serum posaconazole levels among haematological cancer patients taking extended release tablets is affected by body weight and diarrhoea: single centre retrospective analysis

Abstract: The posaconazole extended release tablet formulation was developed to improve bioavailability relative to the oral suspension. Therapeutic drug monitoring has been used to optimise posaconazole dosing to achieve a target trough level ≥0.7 μg ml(-1). We retrospectively evaluated 28 patients with haematological malignancies who received posaconazole tablets for antifungal prophylaxis. Posaconazole serum trough levels were obtained 5 days after initiation of therapy. Mean trough level was 1.19 ± 0.63 μg ml(-1), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
45
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 16 publications
(24 reference statements)
9
45
3
Order By: Relevance
“…The tablet and intravenous formulations were approved on the basis of safety and pharmacokinetic data, with corresponding phase III data for the tablet formulation recently being published (9). To date, several small, single-center studies have reviewed the initial implementation of PCZ tablets, focusing mainly on pharmacokinetic endpoints (5,6,(10)(11)(12). In agreement with our early experience, those reports also have shown that PCZ tablets yield higher serum concentrations than the suspension formulation and appear to be safe (5).…”
supporting
confidence: 66%
See 3 more Smart Citations
“…The tablet and intravenous formulations were approved on the basis of safety and pharmacokinetic data, with corresponding phase III data for the tablet formulation recently being published (9). To date, several small, single-center studies have reviewed the initial implementation of PCZ tablets, focusing mainly on pharmacokinetic endpoints (5,6,(10)(11)(12). In agreement with our early experience, those reports also have shown that PCZ tablets yield higher serum concentrations than the suspension formulation and appear to be safe (5).…”
supporting
confidence: 66%
“…In a study by Miceli et. al., obesity and diarrhea were associated with lower levels (10). Due to limitations with the retrospective nature of the study and medical record documentation, the impact of diarrhea was unfortunately not assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although central nervous system (CNS) toxicity has not previously been reported with posaconazole, this observation may reflect the low levels achieved with the oral suspension combined with its low CNS penetration (7,10). However, newer formulations result in significantly higher posaconazole concentrations in serum (11), particularly in patients with low body mass (12). Use of posaconazole tablets can result in serum concentrations above the range that has been well …”
mentioning
confidence: 73%